Influence of Abiotic Factors on the Growth of Cyanobacteria Isolated from Nakdong River, South Korea1. Issue 3 (20th March 2021) - Yadav, Seema; Anam, Giridhar Babu; Ahn, Young‐Ho
Abstract : Changes in physico‐chemical factors due to natural climate variability and eutrophication could affect the cyanobacterial growth patterns in aquatic systems that may cause environmental health problems. Based on morphological and 16S rRNA gene analysis, three cyanobacterial species isolated for the first time from the Nakdong River water sample in South Korea were identified as Amazoninema brasiliense, Microcystis elabens, and Nododsilinea nodulosa . The variations in temperature, pH, nitrogen, or phosphorus levels significantly impacted the cyanobacterial growth patterns. The optimal temperature range for the growth of isolates was from 25–30°C. A neutral or weak alkaline environment favored growth; however, A. brasiliense resulted in 44.2–87.5% higher biomass (0.75 g · L −1 as dry solids, DS) and growth rate (0.24 · d −1 ) at pH 7 than the other isolates (0.4–0.52 g DS · L −1, 0.16–0.19 · d −1 ). The increased nitrate‐nitrogen (NO3 ‐N) concentrations significantly ( P  < 0.05) favored biomass production and growth rate for A. brasiliense and M. elabens, respectively, and the maximum growth rate was observed for A. brasiliense at 3.5 mg NO3 ‐N · L −1 . The orthophosphate concentration (PO4 –P) from 0.1 to 0.5 mg PO4 ‐P · L −1 increased the growth of the isolates. These observations suggest that isolate growth rates in water bodies can vary depending on different physico‐chemical parameters. This study contributes to the further understanding of the growth of microalgae in natural freshwater bodies under fluctuating environmental conditions and aquatic ecosystem stability.